ANALISIS SIKAP PEDULI LINGKUNGAN SISWA SD NEGERI 184 PEKANBARU - Hadi Gunawan; Guslinda Guslinda (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2019)
The background of this research is the importance of the attitude of caring for the environment that is planted early on starting from the elementary school level. The purpose of this study is to find out how the attitude of caring for students' environment in 184 Pekanbaru Elementary School. This research is quantitative descriptive research type. This research was conducted at 184 Pekanbaru Elementary School. Based on the results of research assessed from 6 indicators, namely cleaning toilets, cleaning trash cans, cleaning the school environment, beautifying classrooms and schools with plants, participating in maintaining parks in schools and participating in maintaining environmental cleanliness. Based on the results of the study showed that 184 Pekanbaru Public Elementary School students have a very caring attitude towards the environment with an acquisition value of 89.02 in the very caring category